The effect of “damai” role-play strategy in group counseling on reducing bullying behavior and enhancing students’ self-regulation - Cici Endang Mustika; Salamiah Sari Dewi; Amanah Surbakti (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Bullying behavior among junior high school students remains a significant concern, particularly in relation to students’ self-regulation abilities. This study aims to examine changes in bullying behavior and self-regulation following group counseling interventions using the “DAMAI” role-play strategy (Listen, Observe, Understand, Invite Interaction). The study employed a one-group pretest–posttest experimental design involving students identified as bullying perpetrators (N = 32). Data were collected using Bullying Behavior and Self-Regulation scales and analyzed using a paired sample t-test. The results showed statistically significant differences between pretest and posttest scores. Bullying behavior scores decreased significantly, while self-regulation scores increased significantly (p < 0.001). These findings indicate that group counseling with the “DAMAI” role-play strategy is associated with positive changes in students’ bullying behavior and self-regulation. The study offers practical implications for Guidance and Counseling teachers in implementing structured group counseling interventions to address bullying in school settings.